2011
DOI: 10.1007/s12311-011-0275-0
|View full text |Cite
|
Sign up to set email alerts
|

Plastic Changes in Striatal Fast-Spiking Interneurons Following Hemicerebellectomy and Environmental Enrichment

Abstract: Recent findings suggest marked interconnections between the cerebellum and striatum, thus challenging the classical view of their segregated operation in motor control. Therefore, this study was aimed at further investigating this issue by analyzing the effects of hemicerebellectomy (HCb) on density and dendritic length of striatal fast-spiking interneurons (FSi). First, we analyzed the plastic rearrangements of striatal FSi morphology in hemicerebellectomized animals reared in standard conditions. Then, since… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 48 publications
0
12
0
Order By: Relevance
“…However, it should be pointed out that ethanol could exert its effect through indirect mechanisms, since PV striatal interneurons are exquisitely susceptible to the modification of neural circuits in which they are involved. For instance, cerebellar damage is a well-documented feature of FASD [27] and it has been demonstrated that hemicerebellectomy leads to a progressive shrinkage of the dendritic tree of striatal interneurons [28]. Moreover, these neurons receive direct projection from corticostriatal neurons [29], mainly located in layer 5 [30].…”
Section: Discussionmentioning
confidence: 99%
“…However, it should be pointed out that ethanol could exert its effect through indirect mechanisms, since PV striatal interneurons are exquisitely susceptible to the modification of neural circuits in which they are involved. For instance, cerebellar damage is a well-documented feature of FASD [27] and it has been demonstrated that hemicerebellectomy leads to a progressive shrinkage of the dendritic tree of striatal interneurons [28]. Moreover, these neurons receive direct projection from corticostriatal neurons [29], mainly located in layer 5 [30].…”
Section: Discussionmentioning
confidence: 99%
“…The cerebellum-basal ganglia pathway starts from the dentate nucleus, goes through the thalamus and reaches the striatum; the basal ganglia-cerebellum pathway starts from the subthalamic nucleus and ends in the cerebellar cortex, passing through the pontine nuclei (Bostan and Strick, 2010; Bartolo et al, 2011). The cerebellum is also thought to be connected with the limbic system, although few anatomical studies are available.…”
Section: The Extended Cerebro-cerebellar Loopsmentioning
confidence: 99%
“…Moreover, these structures are very connected to each other. Th e basal ganglia receive a large amount of input both from the cerebral cortex (Haber, 2016), and cerebellum (Bostan & Strick, 2010;De Bartolo et al, 2011), and their role in cognition is well established (Middleton & Strick, 2000).…”
Section: Physical Activity and Brain Development Are Closely Relatedmentioning
confidence: 99%